KESIAPAN KOMPETENSI AUDITOR DALAM MENJAWAB TANTANGAN KUALITAS AUDIT DI ERA DIGITAL: PERAN MODERASI TEKNOLOGI CYBERSECURITY: AUDITOR COMPETENCY READINESS IN ADDRESSING AUDIT QUALITY CHALLENGES IN THE DIGITAL ERA: THE MODERATING ROLE OF CYBERSECURITY TECHNOLOGY - Priardhina, Isna Diva Nur; Rida Perwita Sari (Universitas Riau, 2025)
This study aims to analyze the effect of auditor competence on audit quality in the digital era with cybersecurity technology as a moderating variable. The study population is auditors working in Public Accounting Firms (KAP) throughout Surabaya. Sampling was carried out using probability sampling techniques with simple random sampling methods to ensure data representativeness. The data obtained were then analyzed quantitatively to test the relationship between auditor competence, cybersecurity technology, and audit quality simultaneously. This research uses the Structural Equation Modeling Partial Least Squares (SEM-PLS) analysis method. The results showed that auditor competence affects audit quality in the digital era. Cybersecurity technology moderates the effect of auditor competence on audit quality in the digital era.